Tissues from equine cadaver ligaments up to 72 hours of post-mortem: a promising reservoir of stem cells. Issue 1 (December 2015) - Shikh Alsook, Mohamad; Gabriel, Annick; Piret, Joëlle; Waroux, Olivier; Tonus, Céline; Connan, Delphine; Baise, Etienne; Antoine, Nadine
Abstract Background Mesenchymal stem cells (MSCs) harvested from cadaveric tissues represent a promising approach for regenerative medicine. To date, no study has investigated whether viable MSCs could survive in cadaveric tissues from tendon or ligament up to 72 hours of post-mortem. The purpose of the present work was to find out if viable MSCs could survive in cadaveric tissues from adult equine ligaments up to 72 hours of post-mortem, and to assess their ability (i) to remain in an undifferentiated state and (ii) to divide and proliferate in the absence of any specific stimulus. Methods MSCs were isolated from equine cadaver (EC) suspensory ligaments within 48–72 hours of post-mortem. They were evaluated for viability, proliferation, capacity for tri-lineage differentiation, expression of cell surface markers (CD90, CD105, CD73, CD45), pluripotent transcription factor (OCT-4), stage-specific embryonic antigen-1 (SSEA-1), neuron-specific class III beta-tubulin (TUJ-1), and glial fibrillary acidic protein (GFAP). As well, they were characterized by transmission electron microscope (TEM). Results EC-MSCs were successfully isolated and maintained for 20 passages with high cell viability and proliferation. Phase contrast microscopy revealed that cells with fibroblast-like appearance were predominant in the culture. Differentiation assays proved that EC-MSCs are able to differentiate towards mesodermal lineages (osteogenic, adipogenic, chondrogenic). Flow cytometry analysis demonstrated that EC-MSCs expressed CD90, CD105, and CD73, while being negative for the leukocyte common antigen CD45. Immunofluorescence analysis showed a high percentage of positive cells for OCT-4 and SSEA-1. Surprisingly, in absence of any stimuli, some adherent cells closely resembling neuronal and glial morphology were also observed. Interestingly, our results revealed that approximately 15 % of the cell populations were TUJ-1 positive, whereas GFAP expression was detected in only a few cells. Furthermore, TEM analysis confirmed the stemness of EC-MSCs and identified some cells with a typical neuronal morphology. Conclusions Our findings raise the prospect that the tissues harvested from equine ligaments up to 72 hours of post-mortem represent an available reservoir of specific stem cells. EC-MSCs could be a promising alternative source for tissue engineering and stem cell therapy in equine medicine.